Black People Against State Harassment (BASH) campaign – a report. (July 2016) - Prescod, Colin
Originally published in The Black Liberator: theoretical and discussion journal for black revolution (1978), the author reports on the inaugural meeting of the Black People Against State Harassment (BASH) campaign. Arguing that sections of the British Left had conflated anti-racism with anti-fascism, the article describes the widely-felt need for Black self defence campaigns, especially against police incursions into Black communities. The author speaks of the need for a broad alliance of Black and Asian resistance to state violence, and hints at the implications that the formation of specialist policing units will have on the working class as a whole.